Comercialización de herbicidas en el Ecuador - Freire Mejía, Gino José (2022)
At present, weeds represent a recurrent problem in most cultivable spaces, causing great economic losses worldwide. The present work was developed with the purpose of knowing the basic aspects regarding the commercialization of herbicides in Ecuador. In Agriculture, herbicides are extensively managed, when used properly, they efficiently control weeds, reducing production costs, otherwise they can cause damage to cultivated plants, human health and ecosystems. Therefore, it is required to have technical knowledge that allows the correct use of herbicides in agriculture, Herbicides are normally marketed in liquid or solid formulations depending on the water solubility of the active ingredient and its form of application, There is a chain of intermediaries to market agrochemicals, which has generated high costs at the time of acquiring the product, for a certain reason it has largely decreased to planting their lands because there is no profit because they do not recover the investment, and those who improve and have benefits are merchants or brokers. The distribution of herbicides in Ecuador plays an important role in the market, where the model of importing bulk product and repackaging in Ecuador is common. where in the case of pesticides, the distributor brand reaches 20% of imports. Herbicides will be marketed wholesale or retail for the purposes indicated in their registration, only in authorized establishments with the proper permits by AGROCALIDAD.